The importance of heterogeneous and homogeneous reactions in oxidative coupling of methane over chloride promoted oxide catalysts - Burch, R; Crabb, E; Squire, G; Tsang, S (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1989)
The formation of ethene from ethane and methane in a silica reactor has been studied both in the presence and in the absence of chloride-containing catalysts. Some homogeneous conversion of ethane to ethene occurs in the gas phase through direct dehydrogenation, oxidative dehydrogenation, and, when HCl is present, chlorine radical induced reactions. Methyl chloride is detected in the gas phase but has no influence on the conversion of ethane to ethene. It is shown that under typical catalytic conditions, when a chloride-modified catalyst is used, ethane is mostly produced in the catalyst bed. © 1989 J.C. Baltzer A.G. Scientific Publishing Company.